Host generalists dominate fungal communities associated with alpine knotweed roots: a study of Sebacinales - Schön,Max Emil; Abarenkov,Kessy; Garnica,Sigisfredo (PeerJ, 2022)
Bistorta vivipara is a widespread herbaceous perennial plant with a discontinuous pattern of distribution in arctic, alpine, subalpine and boreal habitats across the northern Hemisphere. Studies of the fungi associated with the roots of B. vivipara have mainly been conducted in arctic and alpine ecosystems. This study examined the fungal diversity and specificity from root tips of B. vivipara in two local mountain ecosystems as well as on a global scale. Sequences were generated by Sanger sequencing of the internal transcribed spacer (ITS) region followed by an analysis of accurately annotated nuclear segments including ITS1-5.8S-ITS2 sequences available from public databases. In total, 181 different UNITE species hypotheses (SHs) were detected to be fungi associated with B. vivipara, 73 of which occurred in the Bavarian Alps and nine in the Swabian Alps–with one SH shared among both mountains. In both sites as well as in additional public data, individuals of B. vivipara were found to contain phylogenetically diverse fungi, with the Basidiomycota, represented by the Thelephorales and Sebacinales, being the most dominant. A comparative analysis of the diversity of the Sebacinales associated with B. vivipara and other co-occurring plant genera showed that the highest number of sebacinoid SHs were associated with Quercus and Pinus, followed by Bistorta. A comparison of B. vivipara with plant families such as Ericaceae, Fagaceae, Orchidaceae, and Pinaceae showed a clear trend: Only a few species were specific to B. vivipara and a large number of SHs were shared with other co-occurring non-B. vivipara plant species. In Sebacinales, the majority of SHs associated with B. vivipara belonged to the ectomycorrhiza (ECM)-forming Sebacinaceae, with fewer SHs belonging to the Serendipitaceae encompassing diverse ericoid–orchid–ECM–endophytic associations. The large proportion of non-host-specific fungi able to form a symbiosis with other non-B. vivipara plants could suggest that the high fungal diversity in B. vivipara comes from an active recruitment of their associates from the co-occurring vegetation. The non-host-specificity suggests that this strategy may offer ecological advantages; specifically, linkages with generalist rather than specialist fungi. Proximity to co-occurring non-B. vivipara plants can maximise the fitness of B. vivipara, allowing more rapid and easy colonisation of the available habitats.
Keywords: Bistorta vivipara; Belowground fungal communities; Sebacinales; Diversity; Species hypotheses; Generalist; Alpine knotweed; ITS; Sanger sequencing; Global scale